TELAAH FUNGSI PENDIDIKAN ISLAM - Anisa, Anisa; Nurbaya, Siti; Hermawansyah, Hermawansyah (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2024)
This study aims to examine the function of Islamic education from three main dimensions, namely ideological, social, and economic. The research method used is a literature study by collecting data from various primary and secondary literature sources, including relevant books, journals, and articles. The results show that ideologically, Islamic education plays a role in shaping beliefs, character, and morals based on monotheism. From a social perspective, Islamic education serves to instill moral values, justice, and brotherhood to build a harmonious society. Meanwhile, in economic terms, Islamic education prepares individuals to be competent, ethical, and able to contribute to the economic development of the community. Thus, Islamic education has a strategic role in shaping a generation that is faithful, knowledgeable, and productive, which can support the overall progress of society.